CON4EI: SkinEthic™ Human Corneal Epithelium Eye Irritation Test (SkinEthic™ HCE EIT) for hazard identification and labelling of eye irritating chemicals. (June 2018) - Van Rompay, A.R.; Alépée, N.; Nardelli, L.; Hollanders, K.; Leblanc, V.; Drzewiecka, A.; Gruszka, K.; Guest, R.; Kandarova, H.; Willoughby, J.A.; Verstraelen, S.; Adriaens, E.
Abstract: Assessment of ocular irritancy is an international regulatory requirement and a necessary step in the safety evaluation of industrial and consumer products. Although a number of in vitro ocular irritation assays exist, none are capable of fully categorizing chemicals as a stand-alone assay. Therefore, the CEFIC-LRI-AIMT6-VITO CON4EI (CONsortium for in vitro Eye Irritation testing strategy) project was developed with the goal of assessing the reliability of eight in vitro /alternative test methods as well as establishing an optimal tiered-testing strategy. One of the in vitro assays selected was the validated SkinEthic™ Human Corneal Epithelium Eye Irritation Test method (SkinEthic™ HCE EIT). The SkinEthic™ HCE EIT has already demonstrated its capacity to correctly identify chemicals (both substances and mixtures) not requiring classification and labelling for eye irritation or serious eye damage (No Category). The goal of this study was to evaluate the performance of the SkinEthic™ HCE EIT test method in terms of the important in vivo drivers of classification. For the performance with respect to the drivers all in vivo Cat 1 and No Cat chemicals were 100% correctly identified. For Cat 2 chemicals the liquids and the solids had a sensitivity of 100% and 85.7%, respectively. For the SkinEthic™ HCE EIT test method, 100% concordance in predictions (No Cat versus No prediction can be made) between the two participating laboratories was obtained. The accuracy of the SkinEthic™ HCE EIT was 97.5% with 100% sensitivity and 96.9% specificity. The SkinEthic™ HCE EIT confirms its excellent results of the validation studies. Highlights: Concordance in predictions between 2 laboratories was 100%. The obtained accuracy was 97.5%, sensitivity 100% and specificity 96.9%. Drivers of classification: in vivo Cat 1 and No Cat chemicals 100% correct Drivers of classification: in vivo Cat 2100% (L) and 85.7% (S) sensitivity This study confirmed its excellent results observed in the validation studies.